INFLUENCE OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON JOB SATISFACTION WITH EMPLOYEE ENGAGEMENT IN WEST JAKARTA MALLS - Putri*, Indri Youlanda; Rezeki, Fitri (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study uses quantitative methods to examine the effect of work-life balance and work environment on job satisfaction, with employee engagement as an intervening variable among mall employees in West Jakarta. Using the SmartPLS program version 4.0, this study tested the validity, reliability, and causal relationships between variables. The results showed that work-life balance and work environment significantly influence job satisfaction, with employee engagement as a mediating variable. Good work-life balance, low work pressure, job stability, and a comfortable and supportive work environment increase job satisfaction. High employee engagement also contributes positively to job satisfaction, although it weakens the effect of work-life balance. This study concludes that mall management needs to maintain a work-life balance, a good work environment, and enhance employee engagement to achieve optimal job satisfaction. Additionally, survey data indicate that job satisfaction among employees is still relatively low, due to suboptimal work-life balance, work environment, and employee engagement. Improving job satisfaction depends not only on employees but also on various factors within the company. This study provides additional insights into employee engagement as an intervening variable in the impact of work-life balance and work environment on job satisfaction.Â Keywords: Work-Life Balance, Work Environment, Job Satisfaction, Employee Engagement